Sertoli Cell Wt1 Regulates Peritubular Myoid Cell and Fetal Leydig Cell Differentiation during Fetal Testis Development - Wen, Qing (PLoS One, 2016)
Sertoli cells play a significant role in regulating fetal testis compartmentalization to generate testis cords and interstitium during development. The Sertoli cell Wilms’ tumor 1 (Wt1) gene, which encodes ~24 zinc finger-containing transcription factors, is known to play a crucial role in fetal testis cord assembly and maintenance. However, whether Wt1 regulates fetal testis compartmentalization by modulating the development of peritubular myoid cells (PMCs) and/or fetal Leydig cells (FLCs) remains unknown. Using a Wt1(-/flox); Amh-Cre mouse model by deleting Wt1 in Sertoli cells (Wt1(SC-cKO)) at embryonic day 14.5 (E14.5), Wt1 was found to regulate PMC and FLC development. Wt1 deletion in fetal testis Sertoli cells caused aberrant differentiation and proliferation of PMCs, FLCs and interstitial progenitor cells from embryo to newborn, leading to abnormal fetal testis interstitial development. Specifically, the expression of PMC marker genes α-Sma, Myh11 and Des, and interstitial progenitor cell marker gene Vcam1 were down-regulated, whereas FLC marker genes StAR, Cyp11a1, Cyp17a1 and Hsd3b1 were up-regulated, in neonatal Wt1(SC-cKO) testes. The ratio of PMC:FLC were also reduced in Wt1(SC-cKO) testes, concomitant with a down-regulation of Notch signaling molecules Jag 1, Notch 2, Notch 3, and Hes1 in neonatal Wt1(SC-cKO) testes, illustrating changes in the differentiation status of FLC from their interstitial progenitor cells during fetal testis development. In summary, Wt1 regulates the development of FLC and interstitial progenitor cell lineages through Notch signaling, and it also plays a role in PMC development. Collectively, these effects confer fetal testis compartmentalization.